Pesan Dakwah dalam Rubrik Cermin Hati Harian Radar Kudus Jawa Pos - Zaini, Ahmad (Asosiasi Prodi Komunikasi dan Penyiaran Islam (Askopis), 2017)
This paper aims to understand, see and the purpose of the message of the da'wah display of the material of the da'wah messages contained in the